2x+7y=-3 -9x+y=46

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

2x+7y=-3 -9x+y=46

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

too many equal signs
oh my fault i see \[2x+7y=-3\] \[-9x+y=46\] sorry
you want elimination or substitution ?

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

Substitution
then solve second equation for y, because it is easiest \[-9x+y=46\] \[y=9x+46\] and substitute into first equation
2x+7y=-3 (*9) -----> 18x+63y=-27 -9x+y=46 (*2) -----> -18x+2y=92 <=> 65y=65 <=>y=1
2x+7*1=-3 => 2x=-10 => x=-5
You are welcome :p
\[2x+7y=-3\] \[2x+7(9x+46)=-3\] \[65x+322=-3\] \[65x=-325\] \[x=-5\]
the find y by substitution. Alexis got right answer using elimination. doesn't matter which you use
We are both great ^^
Yes, You both are. I just wish I could understand this better... still confused :/
what would an ordered pair be?
Just write what I am writing and if you still have any questions tell me.

Not the answer you are looking for?

Search for more explanations.

Ask your own question